The Mediating Role of Entrepreneurial Orientation in the Relationship between Employee Empowerment and Organizational Commitment - Alhassan, Emad Mohamed Mohamed; Khaled, Afraa Ahmed Mohamed (Journal Research of Social Science, Economics, and Management, 2025)
The business environment is becoming increasingly competitive, compelling companies to constantly innovate and adapt to stay ahead and preserve their competitive advantage in the global market. This research investigates the mediating role of entrepreneurial orientation in the relationship between employee empowerment (including job meaningfulness, ambiguity, and conflict) and organizational commitment within SMEs in Saudi Arabia. Given the critical role of SMEs in economic growth, understanding the factors influencing employee commitment is essential for fostering organizational success. The study employs a quantitative approach with convenience sampling, utilizing survey data from 75 managers of SMEs. The findings reveal that the dimensions of entrepreneurial orientation—autonomy, innovativeness, and risk-taking—significantly influence organizational commitment. Additionally, entrepreneurial orientation partially mediates the relationship between employee empowerment and organizational commitment. This study highlights the importance of entrepreneurial orientation as a key factor in enhancing employee commitment, particularly in the context of SMEs. The implications suggest that organizations should focus on promoting entrepreneurial behaviors to strengthen the link between employee empowerment and organizational commitment, thereby improving overall organizational performance.